Isolated myeloid sarcoma presenting with small bowel obstruction: a case report - Rie Mizumoto; Masanori Tsujie; Tomoko Wakasa; Kotaro Kitani; Hironobu Manabe; Shuichi Fukuda; Kaoru Okada; Shumpei Satoi; Hajime Ishikawa; Toshihiko Kawasaki; Hitoshi Hanamoto; Masao Yukawa; et al. (Surgical Case Reports)
Abstract Background Myeloid sarcoma (MS) is a solid tumor consisting of myeloid blasts or immature myeloid cells, which are unusual outside the bone marrow. Case presentation We present a rare case of isolated myeloid sarcoma of the small bowel in a 54-year-old man who was admitted to our hospital with repeated symptoms of intestinal obstruction. A small bowel series via an ileus tube revealed severe jejunal obstruction. Computed tomography revealed that the obstruction was likely caused by a jejunal tumor. The patient underwent laparoscopy-assisted partial resection of the jejunum with lymphadenectomy. Histopathological examination of the surgical specimen confirmed that MS had been responsible for the obstruction. Conclusions Patients with MS require systemic chemotherapy, as do patients with acute myeloid leukemia. Hence, an early, accurate diagnosis is imperative for treating this malignancy. It is also important to list MS in the differential diagnosis of a small bowel tumor, even in nonleukemic patients.